A symbolic approach for the identification of radiative properties. (July 2017) - Galtier, M.; Roger, M.; André, F.; Delmas, A.
Abstract: A new Symbolic Monte Carlo (SMC) based on null-collision algorithms allows (1) overcoming the usually required knowledge of the optical thickness in SMC and (2) expressing radiative quantities as simple polynomials of the absorption and scattering coefficients. The proposed method can be applied to complex systems such as heterogeneous absorbing and scattering media in complex geometry. It opens new outlooks for the analysis and the identification of radiative properties in a wide range of radiative transfer applications in participating media. Abstract : Highlights: A new symbolic Monte Carlo (SMC) method is proposed for radiative transfer. Quantities are expressed as polynomials of absorption and scattering coefficients. It opens new outlooks for radiative properties identification. It can be applied to complex geometries and heterogeneous participating media.